2012
DOI: 10.1160/th11-11-0795
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of PF4/H multimolecular complex formation with a minimally anticoagulant heparin (ODSH)

Abstract: SummaryRecent studies have shown that ultra-large complexes (ULCs) of platelet factor 4 (PF4) and heparin (H) play an essential role in the pathogenesis of heparin-induced thrombocytopenia (HIT), an immune-mediated disorder caused by PF4/H antibodies. Because antigenic PF4/H ULCs assemble through non-specific electrostatic interactions, we reasoned that disruption of charge-based interactions can modulate the immune response to antigen. We tested a minimally anticoagulant compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…In support of this mechanistic concept, other groups have recently reported that anticoagulant heparin 2-O,3-O-desulfated heparin, a heparinoid molecule, can disrupt PF4:heparin complexes and decrease platelet activation. 34,35 This article describes the initial steps in the identification and characterization of small molecules that bind to specific sites on PF4 and thereby (1) inhibit PF4 tetramerization, (2) inhibit formation of PF4:heparin ULCs, (3) disrupt preformed ULCs, and (4) prevent HIT antibody and Fc␥RIIA-mediated platelet activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this mechanistic concept, other groups have recently reported that anticoagulant heparin 2-O,3-O-desulfated heparin, a heparinoid molecule, can disrupt PF4:heparin complexes and decrease platelet activation. 34,35 This article describes the initial steps in the identification and characterization of small molecules that bind to specific sites on PF4 and thereby (1) inhibit PF4 tetramerization, (2) inhibit formation of PF4:heparin ULCs, (3) disrupt preformed ULCs, and (4) prevent HIT antibody and Fc␥RIIA-mediated platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this mechanistic concept, other groups have recently reported that anticoagulant heparin 2-O,3-O-desulfated heparin, a heparinoid molecule, can disrupt PF4:heparin complexes and decrease platelet activation. 34,35 This article describes the initial steps in the identification and characterization of small molecules that bind to specific sites on PF4 and thereby (1) inhibit PF4 tetramerization, (2) inhibit formation of PF4:heparin ULCs, (3) disrupt preformed ULCs, and (4) prevent HIT antibody and Fc␥RIIA-mediated platelet activation.We also report the development of a robust and reproducible new assay to measure HIT antibodies capable of inducing cellular activation via Fc␥RIIA by transfecting the receptor and an NFATLuc reporter into DT40 cells. We have shown that these cells are activated by the HIT-like monoclonal antibody KKO, as well as by antibodies from several patients with HIT, when PF4 and heparin are present and that activation is via Fc␥RIIA.…”
mentioning
confidence: 99%
“…The amount of UFH needed to reverse these effects and again enhance aPC generation off of TM CS may markedly exceed typical heparinization doses, resulting in a marked anticoagulant effect. However, partially desulfated 2-O, 3-O desulfated heparin (ODSH) has been noted to bind well to PF4, 31 yet it has ≈60-fold less antithrombin activity. 32 We reasoned that ODSH at an optimal level may bind and neutralize much of the free histones and PF4, allowing maximum aPC generation without causing undue anticoagulant effects.…”
mentioning
confidence: 99%
“…Binding of antibodies was then measured by ELISA as previously described. 8 GAGs were purchased from Sigma Aldrich (chondroitin sulfates A and C, dermatan sulfate, dextran sulfate [molecular weight 6500-10 000], and heparan sulfate). Binding of anti-PRT/heparin or anti-PF4/heparin antibodies to PRT/GAGs or PF4/GAGs was performed as previously described.…”
Section: Elisa Studiesmentioning
confidence: 99%